Emplacing god: the social worlds of miracle cities–perspectives from Nigeria and Uganda - Ukah, Asonzeh F. K. (Journal of Contemporary African Studies, 2018)
This paper explores the complex, dynamic and multifaceted transformations in Africa’s religious field through a critical and comparative investigation of two high contrast prayer camps (Miracle Cities), their histories, functions and activities and ownership. The study is based on the ethnography of Prayer Camps in two African cities, Lagos (Nigeria) and Kampala (Uganda), one Pentecostal in orientation, the other, neo-traditionalist in character. The Redemption Camp/City, owned by the Redeemed Christian Church of God, is the largest landmass dedicated to the production and consumption of religion in Africa. The Faith of Unity religious movement, founded by Omukama Ruhanga Owobusozi Desteo Bisaka in Western Uganda, is a neo-traditionalist religious group dedicated to the reinvention of an ‘original’ African spirituality. The paper describes ‘Miracle Cities’ as entheogenic, competitive spaces, symbolic resources and complex social worlds that re-inscribe the importance of space, place and location in the conceptualisation and performance of salvation in Africa. © 2018, © 2018 The Institute of Social and Economic Research.
Paid
Keywords: Nigerian pentecostalism; Owobusobozi; Prayer camps; faith of unity; miracle cities; the redeemed christian church of god